Ratones, ranas y dioses: el esquema ternario de la «Batracomiomaquia» - Esteban, Alicia (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 1991)
«Batrachomyomachia» is a noticeably triadie pocm, both in its structure and its contents. Its composition proves so. it consists of thrcc vesy balanced parts, from whicb the central one •——as well as the rest of it—– shows a perfectly tripartite and proportioned struct’áre. Nevertheless. this formal eharacteristie does not appear unfoundedly, but ir, close connection with its contcnts. On correlating each one of tbe thrcc sections from the central part with the three groups of main characters, the importance of the third charaes:er, the god. –—appaí-ently svith a ¡amor role in dic plot—- iii underlined. Besides, tbe eharacte,- of thc god is overcmphasized by means of such strueiural resources as «Ringkompositions>. which contribute to highlight the two brief seenes wherc the immortal beings appear.